STI in History: Issues and policies in the STI leadership phase. - Lee, Jeong Hyop (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The science, technology, and innovation (STI) system of Korea began to enter a qualitatively different development phase in the 2000s. This is partly because of the limits of the previous catch-up model. As a result, this transition to the Korean system has also been influenced by various political, economic, and environmental issues of global dimensions. The Korean system is now being asked to act as a role model for the development of the international community. The local dimension (which has been neglected in the rapid development of the Korean economy) has emerged to formulate a certain position in the STI initiatives of Korea.